Sedimentary environmental constraints on organic matter enrichment in the coal-bearing Permian Longtan Formation: a case study from NT1H Well, Central Sichuan Basin, China - Yao, Yongjun; Tian, Xuesong; Liu, Maoyao; Liao, Yisha; Peng, Junfei; Guo, Dongxin; Zhang, Ye; Zhang, Yuelei; Tuo, Cong; Chen, Dishu; Chen, Chaogang; Wang, Jinxi; et al. (Frontiers in Earth Science, 2025)
The Permian Longtan Formation (burial depth >2000 m) is a major hydrocarbon-producing unit in central Sichuan Basin, China, and an important heterogeneous unconventional gas reservoir. However, the control of sedimentary environment on organic matter enrichment in its coal-bearing strata remains unclear, hindering deep coalbed methane (CBM) exploration in this region. This study analyzed core samples from NT1H Well using petrological and geochemical methods (e.g., thin-section, X-ray diffraction, trace elements, total organic carbon, FE-SEM, and macerals) to characterize the middle-lower Longtan Formation. It examined how sedimentary environments influence organic matter enrichment and generating-gas capacity (abundance, maturity, and component), revealing key controls. Results show the lithologies in the middle-lower Longtan Formation include mudstone/shale, silty mudstone, and tuffaceous-muddy siltstone-standstone interbedded with multiple thin coal seams, mainly containing clay minerals, quartz, pyrite, and siderite. Horizontal bedding, horizontal-wavy bedding, and parallel bedding are common. Coal seams and their surrounding mudstones/shales have higher organic matter abundances than muddy siltstones-sandstones, indicating strong capacities of organic matter accumulation and gas generation. Coal seams, dominated by vitrinite with minor inertinite, show the highest organic abundance and maturity (TOC 43.76 wt% to 77.97 wt%, R0 >2.5%) than surrounding mudstones/shales. The coal-bearing strata is mainly assigned to lagoon deposits, with two microfacies: sandy-muddy lagoon and peat swamp. The peat swamp is formed by a rapid transformation of muddy lagoon, with sufficient supply of terrestrial materials. These results reveal that the peat swamp microfacies, characterized by weak hydrodynamics and anoxic-to-reducing conditions, is the primary control on the development of multiple thin coal seams, mudstone/shale, and carbonaceous shale, constraining the degree of organic matter enrichment. This study clarifies the sedimentary environmental constraint on organic matter enrichment in the coal-bearing strata, providing a geological basis for evaluating deep CBM resources in central Sichuan Basin.